Política curricular para o ensino de história em Mato Grosso : um estudo sobre o contexto da produção do texto e o contexto da prática - Souza, Leidiane Gomes de (2015)
The policy of Curricular Orientations from Mato Grosso State - Human Science area and History teachers speech about this policy is the object of this master dissertation study. The aim of this study is to analyze the possibilities and difficulties of the implementation of the Curricular Policy proposed by the Education Secretary (2012), through the analysis of the official text and the History teachers’ discourse, on elementary and high public schools in Rondonópolis, Mato Grosso. From the theoretical-methodological viewpoint applied in this study, the reference was the Policy Cycle from Stephen J. Ball and Richard Bowe, as well as the writers Jefferson Mainardes, Alice Casimiro Lopes, Elizabeth Macedo and Eni Orlandi. The corpus of this study was made through the transcription of audio recorded interviews and analyzed based on the interpretation of the aim. It was possible to see that although this policy consists as a guidance tool for the planning of teachers’ actions and it is a result of teachers’ discussions, the interviews, based on the researcher’s view, showed weirdness, detachment and difficulties in relation to the implementation of this policy.